Online Learning Difficulties of The Second-Semester Students of English Language Education Study Program of STKIP PGRI Banjarmasin during COVID-19 Pandemic - Maulidya; Ida Rusdiana; Wulida Makhtuna (English Language Education Study Program of STKIP PGRI Banjarmasin, 2022)
The purpose of this study was to investigate the problems faced by second-semester students at STKIP PGRI Banjarmasin when carrying out online learning process during the covid-19 pandemic. This study follows a quantitative approach in collecting questionnaire data and student interviews. Therefore, this study uses a descriptive method to determine the percentage of online learning difficulties during the covid-19 pandemic. The research sample was taken from 22 students of the second semester of English Education Study Program Academic Year 2020/2021. Data was gathered by questionnaire to confirm students answer and interviews as complementary information from the questionnaire. The results showed that there are two difficulty aspects, the first is an internal factor and the second is an external factor. Internal factors consist of physical barriers in the form of health, and consist of psychological barriers in the form of cognitive, affective and psychomotor. External factors consist of (1) educators (lecturers) in the form of material delivery, assignments and practicum; (2) Facilities in the form of quotas, devices, internet access and books/references; (3) Family in the form of parents and siblings and (4) other activities in the form of activities on and off campus. In general, the difficulties felt the most by second-semester students English Language Education Study Program were internet quotas, internet access, facilities and understanding of the material.